2004
DOI: 10.1002/jgm.559
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfection into fetal sheep airways in utero using guanidinium‐cholesterol cationic lipids

Abstract: These results show that BGTC/DOPE liposomes can mediate gene transfection into the fetal sheep airway epithelium. They also invite the development of optimized BGTC-based formulations and administration conditions with a view to future prenatal gene transfer experiments involving therapeutic genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Thus, because of their transient effect, nonviral vectors may be especially appropriate for the management of congenital abnormalities, such as CDH, in which therapy may only be required for a relatively short time. We have previously shown that BGTC/DOPE liposomes were efficient for gene transfection into the airways of sheep fetus in utero 30. In the present study, we used BGTC/DOPE cationic liposomes to transfect oKGF‐expressing plasmids into the airways of lamb fetuses.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Thus, because of their transient effect, nonviral vectors may be especially appropriate for the management of congenital abnormalities, such as CDH, in which therapy may only be required for a relatively short time. We have previously shown that BGTC/DOPE liposomes were efficient for gene transfection into the airways of sheep fetus in utero 30. In the present study, we used BGTC/DOPE cationic liposomes to transfect oKGF‐expressing plasmids into the airways of lamb fetuses.…”
Section: Discussionmentioning
confidence: 86%
“…In a previous study 30, we investigated the potential utility of bis(guanidinium)‐tren‐cholesterol/dioleoyl‐phosphatidyl ethanolamine (BGTC/DOPE) cationic liposomes for nonviral prenatal lung gene therapy. Plasmids expressing the Escherichia coli chloramphenicol acetyltransferase (CAT) reporter gene were complexed with BGTC/DOPE liposomes and the resulting lipoplexes were administered to sheep fetuses (70 days of gestation) via surgical replacement of the fetal airway fluid by the transfection mixture followed by TO.…”
Section: Introductionmentioning
confidence: 99%
“…3) that efficiently transferred the gene of CFTR into the lungs of cystic fibrosis patients, and alleviated the burden of their ailment (Alton et al, 1999). The replacement of the amines by guanidines led to the design of a new class of cationic cholesterol derivatives, such as bis(guanidinium)-tren-cholesterol (BGTC) that efficiently delivery genes to the airway epithelium of mice and sheeps in vivo (Luton et al, 2004;Vigneron et al, 1996). However, this vector has not been examined in clinical trials yet.…”
Section: Development Of Polyprenoid-based Gene Delivery Systemsmentioning
confidence: 99%
“…Lehn and co-workers reported transfection of foetal sheep airways in utero using guanidinium-cholesterol cationic lipids (117). Gene therapy, to reduce rejection-mediated damage, holds out some promise as a novel therapeutic strategy in corneal transplantation as the donor cornea can easily be manipulated, ex vivo, prior to transplantation (118).…”
Section: Sheep Modelsmentioning
confidence: 99%